The importance of herbal medicine in the treatment of type 2 Diabetes mellitus (Research, Society and Development, 2023)
Type 2 Diabetes Mellitus is a chronic disease that is currently affecting the health of many people, with poor eating habits and a sedentary lifestyle. Phytotherapy is an alternative treatment that has been researched in recent years, as a complementary therapy for glycemic control in patients with DM2. Diabetes is an important target for the search for new treatment methods with the possibility of using various species of medicinal plants. This work aimed to describe the prevalence of use of medicinal and herbal plants considered hypoglycemic by diabetic patients. Medicinal plants and herbal medicines are among the main therapeutic resources of traditional medicine and complementary medicine. The articles found in this first stage of the research were analyzed by reading titles and abstracts that were in accordance with the theme. Finally, the articles were fully evaluated and those most relevant to the focus of the research were selected. The most prevalent medicinal and herbal plants were Bauhinia Forficata (vaca's paw) and Asterceae Baccharis Trimera (Less) DC. (Carqueja), which is the second most cited plant for its hypoglycemic effects. To this end, it was possible to identify studies in the literature that also proved other species and their anti-hyperglycemic actions, seeking to promote the quality of life of patients.